Molecular Study of Antimicrobial Bacteriocins Isolated from Lactobacillus on Pseudomonas aeruginosa - Ali Faleh , Noor; Mohei Mozher , Abbas (ASJ - Academic Science Journal, 2024)
Out of 50 samples of yogurt and vaginal swabs, 20 isolates of Lactobacillus (LAB) were isolated for the current investigation. Additionally, the bacteriocin produced by lactic acid bacteria that produced against Pseudomonas aeruginosa bacteria was screened. The results of morphological, microscopical, and biochemical tests used to identify these isolates showed that they are all of the Lactobacillus genus. Moreover, screening was performed for the best producer isolate and the results showed the yogurt-isolated Lactobacillus bacterium was the best bacteriocin activity according to screening results for the best producer isolate. To isolate the P. aeruginosa-tested bacterium about 100 urine samples from females patients at AlBatool teaching hospital (Diyala/Iraq) with ages ranging from 19 to 40 years were gathered. 34 investigated bacteria in all were isolated. When two antibiotics (Piperacillin 5 mg and Ciprofloxacin 10 mg) were tested for antibiotic susceptibility using the agar disk diffusion method, all isolates appeared to be resistant to Piperacillin and 16% to Ciprofloxacin. Using the micro-titer plate method on four different isolates of P. aeruginosa, both with and without bacteriocin treatments, the producing biofilm was observed. The results showed that bacteriocin treatment resulted in a decrease in biofilm thickness (i.e., biofilm absorbency). Additionally, the minimum inhibitory concentration (MIC) of bacteriocin, determined using the good diffusions method, was 12.5 mg/ml.   The expression of genes PA-ss (species-specific gene) and Ps1A (polysaccharide synthesis locus) before and after bacteriocin treatment was compared using reverse transcription-quantitative quantitative polymerase chain reaction (RT-qPCR). The findings indicate that this gene's folding was reduced following bacteriocin treatment, indicating that bacteriocin inhibits the gene expression in the bacteria that form biofilms to isolate them.